Nietzsche e a genealogia da verdade - Monteiro, Átila Brandão (2016)
This dissertation aims to provide an interpretation about the set of reflections developed by the German philosopher Friedrich Nietzsche around the notion of truth. Such reflection is carried out from different points of view present in his work, trying to observe how articulate the ideas of truth and life, with the thread of the notion of "will to truth". I seek, on the one hand, articulate the moments in which the philosopher undertakes criticism of the notion of truth, first directed to the metaphysical truths, but pointing and investigating at the same time, to the notion of veracity, as it passes the it is understood as the likely source of that. Then attempt to understand, in the wake of reflection on the veracity, how Nietzsche develops this critical and gives it a new direction with an existential and normative sense (since elects a criterion from which to assess the value of moral values), from the preparation of its genealogical procedure. The result of such reflections are essential to understanding the “will to truth” idea and also a possible sense of the truth to the philosopher.